COMPARISON OF GNSS INDICES, IONOSONDES AND ALL-SKY IMAGERS IN MONITORING THE IONOSPHERE IN BRAZIL DURING QUIET AND DISTURBED DAYS - Christovam de Souza, Ana Lucia [UNESP]; Camargo, Paulo de Oliveira [UNESP] (Univ Federal Parana, Centro Politecnico, 2019)
Measurements from the Global Navigation Satellite System (GNSS) have become a leading data source for ionospheric studies. Different technologies are used to monitor the ionospheric layer. It is possible to carry out this monitoring using GNSS networks through the indices of ionospheric irregularities, as well as through ionosondes and imagers. It has therefore become essential to correlate these forms of monitoring, presenting their advantages and disadvantages. With this in mind, the aim of this work was to perform an analysis of the behavior of the ionosphere in the Brazilian region through the ionospheric irregularity indices, along with ionosonde information and all-sky optical imagers, for a day of high solar activity (1 March 2014) and a day of low activity (12 April 2015). The results of each monitoring technique were compatible for the different scenarios, showing a moderate and positive correlation between the irregularity indices (F-P) and ionosonde parameter. The imagers perform measures of greater spatial extent, however, they need favorable meteorological conditions. The ionosondes present a greater diagnostic capacity of the ionosphere but they are fewer in number than the imagers. The GNSS networks become ionosphere monitoring stations through the irregularity indices, enabling an increase in spatial resolution and a better understanding of ionospheric phenomena in the Brazilian territory.
Keywords: Ionospheric irregularities; Ionosonde; Imagers